(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: Research by IDAI shows that although 90% of mothers breastfeed, only 20% exclusively breastfeed for the first six months. In Indonesia, the prevalence of exclusive breastfeeding will reach 72.04% in babies 0-6 months in 2022, with variations between regions. Cultural factors, health knowledge, and family support influence exclusive breastfeeding. Family support and maternal knowledge play an important role. Increased understanding and support is needed to involve all relevant parties. A survey at the Lampihong Community Health Center showed that of 5 mothers with babies over six months, only 2 gave exclusive breastfeeding because they thought it was good and cost-effective. Meanwhile, 3 mothers did not exclusively breastfeed because they followed the family tradition of giving additional foods such as honey and brown sugar. Objective: This study aims to determine whether there is a relationship between family support and mothers’ attitudes towards exclusive breastfeeding in the UPTD work area of the Lampihong Community Health Center. Methods: Quantitative method with a cross-sectional approach Results: 25 (52%) mothers exclusively breastfed. Good family support was 41 (85.42%). Based on the Chi-Square test, 4 cells were found that had an expected count of less than 5, so the alternative Mann-Whiteney test was used with Asymp results. Sig. of 0.788. Conclusion: There is high family support for exclusive breastfeeding at the Lampihong Community Health Center, but the proportion of mothers who provide exclusive breastfeeding is still low. There is no significant relationship between family support and mother’s attitude towards exclusive breastfeeding.